MORPHOLOGICAL FEATURES OF DOXORUBICIN-INDUCED LIVER DAMAGE ASSOCIATED WITH NONALCOHOLIC STEATOHEPATITIS - Maslova, G.S.; Skrypnyk, I.M.; Yeroshenko, G.A. (World of Medicine and Biology, 2020)
The paper consideres the study of histological features of anthracycline-induced liver lesions concomitant with non-alcoholic steatohepatitis.The findings of the study have established the presence of moderate fatty degeneration of the liver with mild focal protein dystrophy of hepatocytes in the lobules of the animals with experimental non-alcoholic steatohepatitis. In the group of animals with anthracycline-induced liver damage, moderate periportal necrosis of hepatocytes along with a mild small-droplet fatty degeneration. Prominent total (centrilobular and periportal) subacute liver necrosis along with moderate fatty degeneration was found in animals with anthracycline-induced liver damage associated with experimental non-alcoholic steatohepatitis.
Keywords: non-alcoholic steatohepatitis; anthracycline-induced liver damage; rats